Electrochemical behavior of carbon/nickel sulfide nanocomposite thin films for advanced energy applications - Ayushi Sharma; Shreya; Peeyush Phogat; Ranjana Jha; Sukhvir Singh (Next Nanotechnology)
The present study focuses on the hydrothermal synthesis of nickel sulfide (NiS) stabilized on carbon nanospheres (CNSs) with varying concentrations of CNSs. The samples were annealed to study the effect on their structural, chemical, and optical properties. Various characterizations were performed to confirm the presence of NiS nanocomposites, to study the annealing effects, and to examine how the increased amount of carbon nanospheres affects the sample properties. X-ray diffraction (XRD) patterns revealed the formation of multiple-phase C/NiS2/NiSO4·6(H2O) nanocomposites, which were observed to be forming CNSs/NiS nanocomposites after annealing, indicating the removal of sulfate impurity. Significant variations in the bandgap and absorption spectra were observed due to the varying concentration of CNSs from 0.3 g to 0.7 g. Morphological study through field emission scanning electron microscope (FESEM) showed the formation of nanosheets of NiS2/NiSO4·6(H2O) over carbon nanospheres, which was reduced to NiS after annealing. Transmission electron microscope (TEM) images of annealed samples showed the formation of CNSs/NiS nanocomposites. Electrochemical studies conducted through cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) showed diffusion-controlled behavior in all samples, rendering samples ideal for solar cell applications with the value of Warburg impedance 116.4 Ohm(s)1/2 for CNS1. Overall, the characterization results provide valuable insights into the properties and behavior of the synthesized nanocomposites.